Managing the complexities of English Language teaching in engineering - Mohamed, Mimi Nahariah Azwani (2015)
In this 21st century, engineering employers seek professional engineers who have excellent scientific knowledge and are able to demonstrate good communication and problem solving skills. With this focus on job demands, engineering education has been restructured, balancing the emphasis between scientific knowledge and soft skills. This shift in focus has not only affected the teaching and learning in engineering education, but also English Language (EL) educators who are involved in teaching non-technical components within an engineering education curriculum. This shift in focus has raised the demand for ESP which include teaching communication skills in English language discourse used in engineering, and teaching problem solving skills in English language teaching. With this demand, challenges are inevitable among EL educators who are generally prepared for teaching English for generic purposes in school settings and who bring with them pedagogical knowledge and beliefs in English language teaching, as well as identities they have developed from their previous to their new workplace. This shift also raises questions about the ways in which English language teaching is positioned, the role of English language courses within an engineering-specific context and the implications of this positioning on the design of the English language courses. The main aim of this study was to investigate how EL educators managed the complexities in teaching English at one technical university in Malaysia. In addressing the research questions, a case study design was developed to highlight the complexities within that context and the ways in which EL educators managed these complexities. The data for this study were collected through qualitative and quantitative methods to unpack the complex process of teaching English for engineering which included teaching problem solving and communication skills. These methods obtained insights into the ways in which EL educators conceptualised English language teaching, positioned themselves and framed their teaching in an engineering context. The quantitative data were collected through a questionnaire involving 12 EL educators. The data from the questionnaire were used to profile the EL educators at the English Language Department of this university. Based on the profiling, four EL educators teaching undergraduate engineering students were selected for the main study. The qualitative data were collected through document study, individual semistructured interviews, classroom observations, video recording of classroom observations and stimulated recall protocols. This study found that there were disconnections between English language teaching and the engineering discipline at this university. These disconnections were due to the dissemination process of the engineering accreditation requirements whereby these requirements went through ii multiple layers of interpretation, adaptation and translation before they reached the EL educators, causing ambiguities in positioning English language teaching and misalignments in the role of the English language courses within the engineering academic curriculum. As a result, tensions occurred in determining the emphasis of English language teaching. The ambiguities in positioning English language teaching and the misalignments of the English language courses presented the EL educators with challenges in managing their pedagogies and framing their teaching within the context of an engineering university. The study found that the strategies that the EL educators exercised in their agency resulted from the interplay between how they positioned English language teaching and the professional identities they developed in their university context. The demand for ESP required these EL educators to teach beyond their expertise, creating challenges for them to establish their professional identities. Complexities emerged when English language teaching involved integration among English language, communication skills, engineering knowledge, and problem solving skills. This study contributed to the field of English language teaching, specifically to English for Specific Purposes (ESP) by providing knowledge and understanding of the complexities of teaching English for the engineering discipline in higher education. It also contributed to research on professional identities by highlighting the tensions, struggles and negotiations that EL educators faced in positioning themselves within this context to determine their professional identities. The findings of this study deepen our knowledge and understanding of professional identities and agency among EL educators in the Malaysian context, particularly in the discipline-specific context of engineering.